Penerapan Projek Penguatan Profil Pelajar Pancasila (P5) tentang Kearifan Lokal pada Kurikulum Merdeka di MIN 1 Kutai Timur - Belawati Pandiangan, Anjani Putri; Rahayu, Resti Novia; Khairunniza Reynaldy, Ainun Zasha (Indonesian Journal of Elementary Education and Teaching Innovation, 2024)
To support the quality of education in Indonesia, the Independent Curriculum concept is implemented through the Pancasila student profile. The Strengthening Pancasila Student Profile Project is present as an effort to develop the character of students' Pancasila student profiles. Through this project, students are invited to observe the surrounding environment in order to find solutions to various existing problems. This research aims to determine the implementation of the Strengthening Pancasila Student Profile (P5) Project activities at MIN 1 East Kutai and its impact on students.  This research uses a qualitative approach.  Qualitative research methods are used as a study of natural object conditions. The approach used by researchers in the research is a qualitative descriptive approach.  Data was collected through observation and interviews with one of the teachers at MIN 1 East Kutai. Through observations and interviews, field notes are produced which researchers use as a consistent data source and support research findings. In implementing the independent curriculum, students create or implement projects. Implementation of P5 activities is one of the independent curriculum project activities. Activities carried out at MIN 1 East Kutai with the theme of Local Wisdom "Food and Batik Typical of Kutai" resulted in P5 activity projects in the form of 1) making Kutai serabi, 2) making typical Kutai pulut rice, 3) making typical Kutai tamarind vegetables, 4) making typical Kutai batik. The result of this research contributes to understanding the importance of implementing the Independent Curriculum and integrating the six Pancasila Student Profiles in learning. This research also provides guidance for educational institutions in integrating the Pancasila Student Profiles in learning and optimizing the implementation of the Independent Curriculum. Thus, this research provides an overview of the importance of thorough preparation in planning P5 activities in order to form a Pancasila Student Profile that is in accordance with the objectives set by the Ministry of Education and Culture, Research and Technology. Keyword: independent curriculum, teacher preparation, local wisdom, project for strengthening pancasila student profiles.